ANALISIS PROFITABILITAS PADA PT. ALWAN ZAHIRA TAHUN 2010-2012 DI SAMARINDA - -, TINA - (EKONOMIA, 2014)
Profitability is the ratio which aims to determine the company's ability to generate profits for a certain period and also give an idea of the effectiveness of management in their operation.The problems of this paper is formulated ; Profitability is at. Alwan Zahira has increased from year 2010-2012 ? By hypothesis Profitability at. Alwan Zahira from 2010 to 2012 has increased. The purpose of this study was to determine the level of profitability. The purpose of this study was to determine the level of profitabitas at. Alwan Zahira in Samarinda from 2010-2012.Basic theory used is financial management by using tools of analysis and hypothesis testing are: Gross Profit Margin , Operating Profit Margin , Net Profit Margin, Return On Investment ( ROI ) and Total Assets Turn Over .Based on these discussions , it is generally known that the ratio of profitability at PT . Alwan Zahira tend to fluctuate from year 2010-2012 , so in this case the authors hypothesis is rejected , given the proposed hypothesis is the author of